Spectropolarimetry of the 3 micron ice feature toward the becklin-neugebauer object 1 - Hough, J; Chrysostomou, A; Messinger, D; Whittet, D; Aitken, D; Roche, P (Institute of Physics Publishing, 1996)
We present spectropolarimetry of the 3.1 μm water-ice feature in the Becklin-Neugebauer (BN) object in OMC-1, with spectral resolution and signal-to-noise ratios substantially improved over previous observations. The well-known increase in polarization within the ice feature is interpreted in terms of a model for aligned graphite and silicate grains with ice mantles. We identify polarization structure in the long-wavelength (3.3-3.6 μm) wing of the ice profile, including a feature at 3.47 μm which matches closely the spectroscopic feature discovered in several protostars and attributed to carbonaceous material with diamond-like structure. We also show, for the first time, the occurrence of a systematic variation in the position angle of polarization across the ice feature in BN, indicating systematic differences in the relative numbers of core-mantle and unmantled grains along the line of sight, and a twist in the magnetic field orientation. © 1996. The American Astronomical Society. All rights reserved.